PENGARUH KOMPENSASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN MELALUI KEPUASAN KERJA PADA PT PDAM TIRTA MOEDAL SEMARANG - Akhmad Andri Nurhuda, 13.05.51.0091 (Students Journal of Economic and Management, 2017)
This study aims to examine the effect of compensation and work environment on employee performance through job satisfaction at PT. PDAM Tirta Moedal Semarang. The population in this research is all employees of PT. PDAM Tirta Moedal Semarang located on Semarang. The data obtained through questionnaires amounting to 119 samples consist of each part to represent the sample. Data analysis method used is quantitative analysis by using validity test, reliability, multiple linear regression test, and test of research model. The results showed that the compensation and work environment both simultaneously and partially have a significant effect on job satisfaction while employee performance variables affect the job satisfaction. Keywords: Compensation, Work Environment, Job Satisfaction and Employee Performance.